Role of T3SS-1 SipD Protein in Protecting Mice against Non-typhoidal Salmonella Typhimurium. - Bakhos Jneid; Karine Moreau; Marc Plaisance; Audrey Rouaix; Julie Dano; Stéphanie Simon (Public Library of Science (PLoS), 2016)
BACKGROUND:Salmonella enterica species are enteric pathogens that cause severe diseases ranging from self-limiting gastroenteritis to enteric fever and sepsis in humans. These infectious diseases are still the major cause of morbidity and mortality in low-income countries, especially in children younger than 5 years and immunocompromised adults. Vaccines targeting typhoidal diseases are already marketed, but none protect against non-typhoidal Salmonella. The existence of multiple non-typhoidal Salmonella serotypes as well as emerging antibiotic resistance highlight the need for development of a broad-spectrum protective vaccine. All Salmonella spp. utilize two type III Secretion Systems (T3SS 1 and 2) to initiate infection, allow replication in phagocytic cells and induce systemic disease. T3SS-1, which is essential to invade epithelial cells and cross the barrier, forms an extracellular needle and syringe necessary to inject effector proteins into the host cell. PrgI and SipD form, respectively, the T3SS-1 needle and the tip complex at the top of the needle. Because they are common and highly conserved in all virulent Salmonella spp., they might be ideal candidate antigens for a subunit-based, broad-spectrum vaccine. PRINCIPAL FINDINGS:We investigated the immunogenicity and protective efficacy of PrgI and SipD administered by subcutaneous, intranasal and oral routes, alone or combined, in a mouse model of Salmonella intestinal challenge. Robust IgG (in all immunization routes) and IgA (in intranasal and oral immunization routes) antibody responses were induced against both proteins, particularly SipD. Mice orally immunized with SipD alone or SipD combined with PrgI were protected against lethal intestinal challenge with Salmonella Typhimurium (100 Lethal Dose 50%) depending on antigen, route and adjuvant. CONCLUSIONS AND SIGNIFICANCE:Salmonella T3SS SipD is a promising antigen for the development of a protective Salmonella vaccine, and could be developed for vaccination in tropical endemic areas to control infant mortality.